Dampak Pemberian Green manure Dan Pupuk Phonska Terhadap Perkembangan Dan Hasil Tanaman Jagung Manis (Zea mays Saccarata L.) - Opier, Putri N J; Matatula, Avia J; Marasabessy, Dessy A (Universitas Pattimura, 2024)
This study aims to evaluate how green manure applied with Chromolaena odorata and Gliricidia sepium leaves, along with NPK compound fertilizer (phonska), affects the growth and yield of sweet corn (Zea mays saccharata L.). Conducted in Telaga Kodok, Central Maluku, from September to November 2022, the experiment utilized factorial design with varying doses of green manure (0, 10, and 20 tons per hectare) and phonska fertilizer (0%, 50%, and 100% of the recommended dose). Observed parameters included plant height, leaf count, leaf area, leaf area index, cob length, cob weight with husk, cob weight without husk, and cob diameter. The results of the ANOVA analysis indicate that both factors and their interaction significantly influence sweet corn's growth and yield parameters. It is recommended to apply 20 tons of green manure per hectare and 100% phonska dose to achieve optimal results, considering parameters such as plant height, leaf count, leaf area, cob length, cob weight with and without husk, and cob diameter. By enhancing sweet corn productivity, supporting food security, and promoting sustainable agricultural sector growth, this research significantly contributes to optimizing the use of organic and inorganic fertilizers.